Aplicação da técnica espectroscopia de impedância eletroquímica em análises de corrosão de revestimentos não convencionais de cromo duro em meio aquoso contendo cloretos - Dantas , Valdessandro Farias (Universidade Federal Rural do Semi-Árido, 2021)
Electroplating is one of the most used processes in obtaining metallic coatings. Its application allows the control of several parameters, such as current and potential density, temperature and process agitation. These in turn significantly influence the chemical composition, microstructure and layer thickness of the deposits obtained. Among the metals used as electrodeposits, chromium stands out, obtained industrially from conventional hard chromium baths based on CrO3. As technology advanced, it became necessary to improve these baths in order to improve the quality of deposits. In the last two decades, there has been a growing interest in the development of new formulations capable of providing hard chrome coatings with exceptional characteristics, in relation to hardness, resistance to mechanical wear and corrosion. It is currently known that an adequate addition of complexing agents to electrolytes can enable the synthesis of coatings with excellent properties, these in general are called unconventional chromium baths. The corrosion resistance of these electrodeposits is generally evaluated using electrochemical techniques, including electrochemical impedance spectroscopy (EIS). This technique allows obtaining important kinetic parameters of the process, such as the polarization resistance. In this work, an EIS technique is used to analyze the corrosion resistance of hard chromium deposits, obtained from non-conventional dichromate baths in a chloride-containing medium.
Keywords: Cromo; Eletrodeposição; Impedância; Complexantes; Eletroquímica; ENGENHARIAS::ENGENHARIA QUIMICA